Applying bioethical principles to human biomonitoring - Harrison Myron (BMC, 2008)
Abstract Bioethical principles are widely used as a normative framework in areas of human research and medical care. In recent years there has been increasing formalization of their use in public health decisions. The "traditional bioethical principles" are applied in this discussion to the important issue human biomonitoring for environmental exposures. They are: (1) Autonomy - Also known as the "respect for humans" principle, people understand their own best interests; (2) Beneficence - "do good" for people; (3) Nonmaleficence - "do no harm"; (4) Justice - fair distribution of benefits and costs (including risks to health) across stakeholders. Some of the points made are: (1) There is not a single generic bioethical analysis applicable to the use of human biomonitoring data, each specific use requires a separate deliberation; (2) Using unidentified, population-based biomonitoring information for risk assessment or population surveillance raises fewer bioethical concerns than personally identified biomonitoring information such as employed in health screening; (3) Companies should proactively apply normative bioethical principles when considering the disposition of products and by-products in the environment and humans; (4) There is a need for more engagement by scholars on the bioethical issues raised by the use of biomarkers of exposure; (5) Though our scientific knowledge of biology will continue to increase, there will always be a role for methods or frameworks to resolve substantive disagreements in the meaning of this data that are matters of belief rather than knowledge.